2016
DOI: 10.18410/jebmh/2016/618
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Gastric Mucosal Biopsies in Chronic Gastritis Patients With Special Correlation to Helicobacter Pylori Infection at Rims Hospital

Abstract: BACKGROUND Chronic gastritis is a common condition in general population. Of the many aetiological factors, Helicobacter pylori is one of the primary cause of chronic gastritis. AIMS  To study the histopathological features of chronic gastritis associated with H. pylori infection.  To find out the relationship between severity of inflammatory reaction in gastritis and intensity of H. pylori. MATERIALS This cross sectional study was carried out in Regional Institute of Medical Sciences (RIMS) Hospital from Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…10 Choudhury et al reported 65% of chronic gastritis subjects in India were male. 11 While the study by Siregar GA in Medan in 2015 exhibited that 51.25% of subjects with chronic gastritis were male. 12 The mean of chronic gastritis patients in this study was 49.25 years old, which was classified as productive age.…”
Section: Discussionmentioning
confidence: 99%
“…10 Choudhury et al reported 65% of chronic gastritis subjects in India were male. 11 While the study by Siregar GA in Medan in 2015 exhibited that 51.25% of subjects with chronic gastritis were male. 12 The mean of chronic gastritis patients in this study was 49.25 years old, which was classified as productive age.…”
Section: Discussionmentioning
confidence: 99%